THE APPLICATION OF RISK MANAGEMENT TO MINIMIZE THE RISK OF BAD DEBTS IN PT. BANK MANDIRI - Dwi Urip Wardoyo; Emeralda Diva Vania; Septiani Wahyuningrum (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
The important sector in economic growth in Indonesia is the banking sector. The banking sector is a community fund collection institution. Until now the existence of the banking sector has increased, it also makes there an increase in risk. This increase is characterized by the increasing distribution of public funds to the banking sector. Due to the large amount of these funds, as for the regulations issued by Bank Indonesia regarding the implementation of risk management for commercial banks with Bank Indonesia Circular Letter No.7/3DPNP dated January 31, 2015. This research aims to find out the application of risk management at PT Bank Mandiri. The type of research is descriptive research with a qualitative approach. The results of this study show that PT Bank Mandiri has implemented good risk management to minimize problem credit well in accordance with the provisions of Bank Indonesia and is able to maintain the average level of Non-Performing Loan (NPL), the NPL figure will show the percentage of problematic credit from all credits launched to the public.